Patient-Perceived Pressure from Clinicians for Labor Induction and Cesarean Delivery: A Population-Based Survey of U.S. Women - Jou, Judy (Health Serv Res, 2015)
OBJECTIVE: To determine whether patient-perceived pressure from clinicians for labor induction or cesarean delivery is significantly associated with having these procedures. DATA SOURCES/STUDY SETTING: Listening to Mothers III, a nationally representative survey of women 18–45 years who delivered a singleton infant in a U.S. hospital July 2011–June 2012 (N = 2,400). STUDY DESIGN: Multivariate logistic regression analysis of factors associated with perceived pressure and estimation of odds of induction and cesarean given perceived pressure. PRINCIPAL FINDINGS: Overall, 14.8 percent of respondents perceived pressure from a clinician for labor induction and 13.3 percent for cesarean delivery. Women who perceived pressure for labor induction had higher odds of induction overall (adjusted odds ratio [aOR]: 3.51; 95 percent confidence interval [CI]: 2.5–5.0) and without medical reason (aOR: 2.13; 95 percent CI: 1.3–3.4) compared with women who did not perceive pressure. Those perceiving pressure for cesarean delivery had higher odds of cesarean overall (aOR: 5.17; 95 percent CI: 3.2–8.4), without medical reason (aOR: 6.13; 95 percent CI: 3.4–11.1), and unplanned cesarean (aOR: 6.70; 95 percent CI: 4.0–11.3). CONCLUSIONS: Patient-perceived pressure from clinicians significantly predicts labor induction and cesarean delivery. Efforts to reduce provider–patient miscommunication and minimize potentially unnecessary procedures may be warranted.